The impact of 32 days' exposure to hypobaric hypoxia on physiological cost of sub-maximal work performed at the sea level - Kujach, S.; Grzywacz, T.; Ziemann, E.; Szymczak, R.; Luszczyk, M.; Laskowski, R. (Baltic Journal of Health and Physical Activity, 2011)
Background: Many papers showed that long-lasting exposure to hypobaric hypoxia changed the metabolic cost of work and substrate contribution, elevating exercise energy expenditure and carbohydrates utilization. Only few of them have shown how long this adaptive changes are maintained. The aim of the study was to assess the impact of prolonged sojourn at high altitude on the physiological cost of sub-maximal work performed at the sea level.